Kinetics and Energetics of Intramolecular Electron Transfer in Single-Point Labeled TUPS-Cytochrome c Derivatives - Khoroshyy, Petro; Tenger, Katalin; Chertkova, Rita V; Bocharova, Olga V; Kirpichnikov, Mikhail P; Borovok, Natalia; Groma, Géza I; Dolgikh, Dmitry A; Kotlyar, Alexander B; Zimányi, László (Molecules (Basel, Switzerland), 2021)
Electron transfer within and between proteins is a fundamental biological phenomenon, in which efficiency depends on several physical parameters. We have engineered a number of horse heart cytochrome c single-point mutants with cysteine substitutions at various positions of the protein surface. To these cysteines, as well as to several native lysine side chains, the photoinduced redox label 8-thiouredopyrene-1,3,6-trisulfonate (TUPS) was covalently attached. The long-lived, low potential triplet excited state of TUPS, generated with high quantum efficiency, serves as an electron donor to the oxidized heme c. The rates of the forward (from the label to the heme) and the reverse (from the reduced heme back to the oxidized label) electron transfer reactions were obtained from multichannel and single wavelength flash photolysis absorption kinetic experiments. The electronic coupling term and the reorganization energy for electron transfer in this system were estimated from temperature-dependent experiments and compared with calculated parameters using the crystal and the solution NMR structure of the protein. These results together with the observation of multiexponential kinetics strongly support earlier conclusions that the flexible arm connecting TUPS to the protein allows several shortcut routes for the electron involving through space jumps between the label and the protein surface.
Keywords: Models, Molecular; Cytochromes c; cytochrome c; Point Mutation; transport elektronů; zvířata; Protein Conformation; hem; pyreny; koně; cytochromy c; konformace proteinů; TUPS; time-resolved spectroscopy; molekulární modely; bodová mutace; oxidace-redukce; intramolecular electron transfer; Heme; Kinetics; Horses; kinetika; Animals; Cysteine; triplet excited state; Oxidation-Reduction; cystein; Electron Transport; Pyrenes